Application of the Principle of Accountability in the Management of National Health Insurance Funds in General Hospitals - Nurul Hikmah M Hasan; Muthi'ah Alamri; Fatmawati Arini Dali (Bacarita Law Journal, 2026)
This study aims to see how the application of the principle of accountability in the performance of General Hospitals to the management of national health insurance. Improving the performance of General Hospitals is essential to ensure good healthcare and meet the needs of the community. However, to achieve that, we need to understand how the principle of accountability is applied in hospital management. The method used in this study is juridical normative. The data used are derived from the relevant literature and previous data. The results of the study show that the implementation of accountability significantly improves budget performance with the concept of value for money, so that the use of the budget becomes more economical, efficient, and effective. The most effective strategies involve strong internal controls and performance-based budgeting that supports transparency and accountability. The implementation of this strategy is able to optimize the use of resources and improve the quality of financial management in the organization. The results of the study provide recommendations to strengthen accountability mechanisms as a strategic step in encouraging sustainable budget efficiency, and the role of local governments in supporting accountability principles is urgently needed. This includes conveying clear information, handling input and complaints from the public, and developing an organized reporting system, among other things. The application of accountability principles is essential to improve the performance of public hospitals. However, greater and sustained efforts are needed from all parties involved to ensure that the principle of responsibility in the management of health insurance funds is not just a buzzword, but is actually applied in every part of hospital operations.